Friends, lovers, chocolate - McCall Smith, Alexander, 1948- (New York : Anchor Books/Random House, 2006)
Taking on the running of her niece's deli while Cat is attending a wedding in Italy, Isabel Dalhousie encounters a recent heart transplant patient who is troubled by memories of events that never happened to him.
Gently starchy Edinburgh ethicist Isabel Dalhousie slips into another sedate but vexing mystery.
"The Sunday Philosophy Club"--Cover.
Sequel to: The Sunday Philosophy Club.
Keywords: Women editors -- Fiction; Heart -- Transplantation -- Patients -- Fiction; Italians -- Scotland -- Fiction; Delicatessens -- Fiction; Housekeepers -- Fiction; Nieces -- Fiction; Edinburgh (Scotland) -- Fiction; Mystery fiction